JUARA GLOBAL SCHOOL STRATEGIC INVESTMENT FORINVESTORS - Sholahuddin Al Ayyubi, Muhammad
The viability of an investment opportunity in the education sector is crucial for potential investors seeking long-term returns and sustainable growth. This study presents a comprehensive financial projection and feasibility analysis of Juara Global School (JGS), a prominent educational institution by Indonesia Juara Foundation that is poised for expansion. The primary objective of this research is to provide investors with valuable insights into the potential profitability and financial feasibility of investing in JGS.